Evaluar diferentes niveles de Betaína como promotor de crecimiento en el rendimiento productivo de pollos Broiler en la Quinta Experimental Punzara de la Universidad Nacional de Loja - Poma Ramírez, Patricia Yessenia (2015)
The present work was carried out in the city of Loja, in the Poultry Program of the Punzara Experimental Ranch, warehouse No.2, belonging to the School of Veterinary Medicine and Zootechnics of the Agricultural and Renewable Natural Resources Area of the National University of Loja. The purpose of the study was to assess levels of betaine as a growth agent of natural origin as an alternative to improve: productive yield, health and animal welfare, without affecting the health of the consumer. Field work was carried out with 400 one day old chickens from the Ross 308 line which were divided into four treatments of 100 chickens each, with four replications. A completely randomized experimental design was used, evaluating the following treatments: T1 (control) received 0mg of betaine; T2 (125mg betaine) had ½cc of betaine per litre of water applied; T3 (250mg betaine) had a dose of 1cc of betaine per litre of water added, T4 (375mg betaine) received a dose of 1½cc of betaine per litre of water. Each treatment with four replications, consisted of 25 chickens each experimental unit. The study lasted for 42 days. The results obtained from the different variables studied are as follows: the largest increase of weight was obtained by treatment two with 2890g; the largest consumption of food was registered in treatment one with 4485g; the best feed conversion was reached in treatment two with 1.55; the lowest mortality rate was treatment one with 3%, in terms of profitability, treatment two was found to be the most profitable with 35.98%.